SBMI Banten As An Intermediary Actor In Dealing With Human Trafficking In Migrant Workers In Serang District - Nissa, Fahdah Fahrun; Hikmawan, M. Dian (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
Human trafficking is a form of crime that can be a threat to human security. Serang Regency is one of the active areas in contributing TKI (migrant workers) due to economic factors and low education. SBMI Banten is present as an intermediary actor who fights for matters related to migrant workers' problems. This study uses the theory of political representation put forward by Olle Tornquist (2009) with three indicators namely demos, intermediary ways, and public affairs. The research method used is a qualitative method with an instrumental case study approach. The results of this study are to explain SBMI Banten as a civil society organization that operates as an intermediary actor in overcoming the problem of human trafficking in migrant workers in Serang Regency.